TATA KELOLA TEKNOLOGI INDORMASI PADA SMK AVERUS MENGGUNAKAN FRAMEWORK CONTROL OBJECTIVES FOR INFORMATION AND RELATED TECHNOLOGY (COBIT) VERSI 4.0 - Handayani, Rani Irma (LPPM Universitas Nusa Mandiri, 2012)
In education, advancement in information technology also contributed significantly. This study aims to provide an assessment of IT governance that already exists and provide an IT governance model proposed for Senior High School Averus Jakarta by referring to the standard COBIT (Control Objective for Information and Related Technology) Version 4.0. COBIT is one methodology that provides the basic framework in creating appropriate information technology with organizational needs while considering other factors that influence. Basically, COBIT was developed to help meet the diverse needs of management by bridging the information gap between business risks, control, and engineering problems. COBIT provides a practical step through the domain and framework that describes the IT activity in a structure and process that can be adjusted. This study uses four COBIT domain, namely Planning and Organisation (PO) and Acquisition and Implementation (AI) Control Objectives but used only 15 of the 34 processes only existing processes.